Gas turbine compressor fouling and washing in power and aerospace propulsion - Igie, Uyioghosa (ASME, 2017)
This paper presents a well-researched subject area within academia, with a high degree of application in the industry. Compressor fouling effect is one of the commonest degradations associated with gas turbine operations. The aim of this review is to broadly communicate some of the current knowledge while identifying some gaps in understanding, in an effort to present some industry/operational interest for academic research. Likewise, highlight some studies from academia that present the current state of research, with their corresponding methods (experimental, numerical, actual operations, and analytical methods). The merits and limitations of the individual method and their approaches are discussed, thereby providing industry practitioners with a view to appreciating academic research outputs. The review shows opportunities for improving compressor washing effectiveness through computational fluid dynamics (CFD). This is presented in the form of addressing the factors influencing compressor washing efficiency. Pertinent questions from academic research and operational experiences are posed, on the basis of this review.
Keywords: Gas turbine; Jet engine; Degradation; Fouling; Compressor washing; Maintenance